Soft magnetic iron-based powder and its manufacturing method, and soft magnetic parts
By using a soft magnetic iron powder with a specific insulating layer and manufacturing process, the iron loss issue in SMCs at frequencies below 1000 Hz is addressed, resulting in improved magnetic performance and reduced energy losses.
Patent Information
- Application Number
- JP2023504802
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-07
- Filing Date
- 2021-01-15
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-01-15
AI Technical Summary
Soft Magnetic Composites (SMC) exhibit higher iron loss at frequencies below 1000 Hz compared to laminated electric steel sheets, limiting their application in motors and other electrical equipment.
A soft magnetic iron powder with an insulating layer containing Si, Al, Mn, and O on its outer surface, manufactured by cooling molten steel with specific compositions and then atomizing and powdering, is used to create a soft magnetic component with reduced iron loss.
The proposed solution effectively reduces iron loss in the frequency range below 1000 Hz, achieving iron loss values of 140 W/kg or less at 1T and 1000Hz, while maintaining excellent magnetic properties and high resistivity.
Smart Images

Figure 0007660187000001 
Figure 0007660187000002 
Figure 0007660187000003
Abstract
Description
[Technical field]
[0001] The present invention relates to soft magnetic iron-based powder, a method for producing the same, and a soft magnetic part. [Background technology]
[0002] Soft magnetic materials are used in inductors for electrical equipment, stator and rotor parts for motors and generators for rotary drive, actuators, sensors, transformer cores, etc. Soft magnetic materials can be manufactured by laminating electrical steel sheets, and among soft magnetic materials, soft magnetic composites (SMCs) are manufactured by coating soft magnetic iron-based powder with an insulating material and compressing and sintering it at high temperatures together with a lubricant or binder. Unlike the two-dimensional method of laminating electrical steel sheets, SMCs allow for three-dimensional electromagnetic field design, and also have the advantage of allowing high design freedom and greatly increasing complexity. However, although SMCs usually have lower iron loss and superior magnetic properties than materials made of laminated electrical steel sheets at high frequencies of 10 kHz or more, they have higher iron loss than materials made of laminated electrical steel sheets in the main driving range of motors below 1000 Hz. Therefore, in order to apply SMCs to materials such as motors, it is important to reduce iron loss in the frequency range below 1000 Hz.
[0003] Iron loss is broadly classified into hysteresis loss and eddy current loss. Hysteresis loss occurs when a magnetic material is magnetized in response to changes in the electromagnetic field generated by AC electricity, while eddy current loss occurs when an induced current occurs in response to changes in the electromagnetic field generated by AC electricity. Normally, hysteresis loss is important at low frequencies, but at high frequencies, eddy current loss accounts for the majority of the total iron loss. SMC has superior eddy current loss characteristics compared to thin plates, so iron loss is low at 10 kHz or higher, but its inferior hysteresis characteristics limit its use below 1000 Hz. Hysteresis loss is proportional to 1 / (√Gs), and eddy current loss is proportional to (√Gs), where Gs is the grain size in a metal. Therefore, in order to reduce iron loss, it is necessary to properly adjust the optimum grain size range. The optimum grain size is also affected by the resistivity of the material; the higher the resistivity, the larger the grain size will be, and the lowest iron loss will be. This is related to the fact that materials with high resistivity have reduced eddy current loss; that is, the higher the resistivity, the lower the iron loss.
[0004] As a method for increasing the resistance, in SMC, a method of applying an insulating coating to iron-based powder particles is known. For example, Patent Documents 1, 2, and 3 present a technique for forming an insulating coating using an inorganic substance. A coating of an organic substance is known, for example, in Patent Document 4. A coating containing both inorganic and organic materials is known, for example, in Patent Documents 5, 6, and 7. According to these documents, iron-based powder particles are coated with an iron phosphate layer and a thermoplastic material. However, this method has drawbacks in terms of manufacturing and cost, since it requires coating with a separate insulating material or adding a binder. In particular, when using a separate insulating material for coating, it is difficult to make the thickness of the coating layer for each powder particle consistent, and it is difficult to select an appropriate insulating material considering the physical / chemical reaction between the powder and the insulating material. In addition, the specific gravity of the iron in the material is reduced by the thickness of the insulating material on the powder, which results in a problem of low energy density per unit volume and low saturation magnetic flux.
[0005] There is a demand for the development of soft magnetic iron-based powders having low iron loss even in the frequency range of 1000 Hz or less, a manufacturing method thereof, and soft magnetic parts, in comparison with conventional iron-based powders and parts manufactured from the powders. In addition, there is currently a need for a method for more efficiently increasing the resistance of iron-based powder without using an insulating material that coats the iron-based powder in order to increase the resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] U.S. Patent No. 6,309,748 [Patent Document 2] U.S. Patent No. 6,348,265 [Patent Document 3] U.S. Patent No. 6,562,458 [Patent Document 4] U.S. Pat. No. 5,595,609 [Patent Document 5] U.S. Patent No. 6,372,348 [Patent Document 6] U.S. Pat. No. 5,063,011 [Patent Document 7] West German Patent No. 3,439,397 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above-mentioned problems, the present invention provides a soft magnetic iron-based powder having low core loss in a frequency range of 1000 Hz or less, a manufacturing method thereof, and a soft magnetic part. [Means for solving the problem]
[0008] As a means for achieving the above object, a soft magnetic iron-based powder according to one embodiment of the present invention includes an insulating layer containing Si, Al, Mn, and O on its outer surface, and is characterized in that it is composed of, by weight percent, Si: more than 2%, Al: more than 0.02%, Mn: more than 0.05%, O: more than 0% but less than 0.1%, with the balance being Fe and unavoidable impurities, and is capable of satisfying [Si] / [Al]>2. The [Si] and [Al] refer to the weight percent of each element.
[0009] In addition, each soft magnetic iron-based powder of the present invention has a D 10 and D. 90The difference between [Si]+[Al]+[Mn] in the above formula may be less than 10% by weight, where [Si], [Al] and [Mn] represent the weight percentages of each element. Moreover, each soft magnetic iron-based powder of the present invention may have an average particle size of 150 to 400 μm. In addition, each soft magnetic iron-based powder of the present invention has a D 95 is less than 500 μm, and D 50 may be 150 to 300 μm.
[0010] As another means for achieving the above object, a method for producing soft magnetic iron-based powder according to one embodiment of the present invention includes the steps of: cooling molten steel, which is composed of, by weight, more than 2% Si, more than 0.02% Al, more than 0.05% Mn, more than 0% but less than 0.1% O, with the balance being Fe and unavoidable impurities, to 1500°C to 1000°C within 10 minutes to solidify the powder; cooling from 1000°C to 900°C or less within 100 minutes; heating to liquidize the powder; and atomizing and powdering the powder, wherein in the solidifying step, the ratio of the specific surface area to the volume of the solidified molten steel is 4 cm. -1 The present invention is characterized in that:
[0011] As another means for achieving the above object, a soft magnetic part according to one embodiment of the present invention comprises soft magnetic iron-based powder containing, by weight, more than 2% Si, more than 0.02% Al, more than 0.05% Mn, more than 0% but less than 0.1% O, with the remainder being Fe and unavoidable impurities, and an insulating layer containing Si, Al, Mn, and O on an interface between the soft magnetic iron-based powder, and is characterized in that it is 140 W / kg or less at 1 T, 1000 Hz.
[0012] In each soft magnetic part of the present invention, the insulating layer may have a thickness of 10 to 50 nm. In addition, each soft magnetic part of the present invention has a G 10 and G 90 The difference between [Si]+[Al]+[Mn] in the above formula may be less than 10% by weight, where [Si], [Al] and [Mn] represent the weight percentages of each element. In each soft magnetic part of the present invention, the area ratio of the soft magnetic iron-based powder having a ratio of the major axis length to the minor axis length of 1 to 2 may be 50% or more. In each soft magnetic part of the present invention, the soft magnetic iron-based powder may have an average size of 150 to 500 μm.
[0013] In addition, each soft magnetic part of the present invention has a G 95 is less than 500 μm, and G 50 may be 150 to 300 μm. Additionally, each soft magnetic component of the present invention may be 40 W / kg or less at 1 T, 400 Hz. In addition, each soft magnetic part of the present invention has a magnetic flux density (B 100 ) may exceed 1.1T. Furthermore, each soft magnetic component of the present invention may have a resistivity exceeding 40 μΩ·cm. Effect of the Invention
[0014] According to the present invention, it is possible to provide a soft magnetic iron-based powder having low core loss in a frequency range of 1000 Hz or less, a method for producing the same, and a soft magnetic part. Furthermore, according to the present invention, it is possible to provide an iron-based powder containing an insulating layer on the outer surface without using a separate insulating material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A soft magnetic iron-based powder according to one embodiment of the present invention includes an insulating layer containing Si, Al, Mn, and O on the outer surface, and contains, by weight percent, Si: more than 2%, Al: more than 0.02%, Mn: more than 0.05%, O: more than 0% but less than 0.1%, with the balance being Fe and unavoidable impurities, and can satisfy [Si] / [Al]>2. The [Si] and [Al] refer to the weight percent of each element.
[0016] In the following, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. The terms used in this application are merely used to describe specific examples. Therefore, singular expressions include plural expressions unless the context clearly requires singularity. In addition, it should be noted that the terms "include" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.
[0017] In addition, unless otherwise defined, all terms used in this specification should be considered to have the same meaning as that generally understood by a person having ordinary knowledge in the technical field to which the present invention belongs. Therefore, unless clearly defined in this specification, a specific term should not be interpreted in an overly ideal or formal sense. For example, in this specification, a singular expression includes a plural expression unless there is a clear exception in the context. In addition, in this specification, the terms "about," "substantially," and the like, when given manufacturing and material tolerances inherent in the stated meaning, are used to mean a numerical value or a approximation thereof, and are used precisely to aid in the understanding of the present invention, or to prevent unscrupulous infringers from unfairly exploiting the disclosure in which an absolute numerical value is stated.
[0018] In addition, in this specification, "D x " refers to iron-based powder particles whose accumulated particle size on the particle size cumulative distribution of iron-based powder particles corresponds to x%, where x is a rational number greater than 0 and less than 100. For example, if x is 10, it refers to iron-based powder that shows a value in the bottom 10% of the particle size measurement results of the iron-based powder. In this specification, "G y " means iron-based powder particles in a component whose accumulated particle size on the particle size cumulative distribution of iron-based powder particles in the component corresponds to y%, where y is a rational number greater than 0 and less than 100. For example, if y is 10, it means iron-based powder that shows a value in the bottom 10% in the particle size measurement results of iron-based powder in the component.
[0019] Soft magnetic iron-based powder is the most important material for manufacturing soft magnetic parts. The soft magnetic iron-based powder according to the present invention includes an insulating layer containing Si, Al, Mn, and O on the outer surface. The insulating layer of the present invention is not formed by coating the iron-based powder with a separate organic / inorganic insulating material as in the past, but is formed by slowly cooling the oxide layer mixed with the powder at the top of the molten metal during powder production. Considering this, the present invention has the advantage of being able to form an insulating layer on the outer surface of the iron-based powder without performing a separate insulating coating as in the past.
[0020] According to one example, the thickness of the insulating layer may be 10 to 50 nm. If the thickness of the insulating layer is less than 10 nm, the insulating properties may be insufficient, and eddy current loss may increase, which may increase iron loss. If the thickness of the insulating layer exceeds 50 nm, the amount of oxygen in the steel may increase significantly, which may be detrimental to magnetic properties.
[0021] In addition, from the viewpoint of further improving the soft magnetic properties, the management of particle size and components is important. The soft magnetic iron-based powder according to an example may have an average particle size of 150 to 400 μm. If the average particle size is less than 150 μm, the hysteresis loss cannot be sufficiently reduced, and the iron loss may not be sufficiently reduced in the low frequency band of 1000 Hz or less. On the other hand, if the average particle size exceeds 400 μm, the eddy current loss increases, and the interval between each particle cannot be sufficiently narrowed during molding under conditions such as high temperature and high pressure, resulting in a problem of low density of the manufactured parts. The average particle size may more preferably exceed 200 μm, and under such conditions, the hysteresis loss is sufficiently reduced and the eddy current loss generated in each particle is not large. In addition, the average particle size is more preferably less than 300 μm, and under such conditions, the local stress concentrated in the part during molding of each powder particle under high temperature and high pressure conditions can be alleviated.
[0022] According to one embodiment of the present invention, 95 is less than 500 μm, and D 50 may be 150 to 300 μm. 95 If the diameter is more than 500μm, the surrounding small particles cannot receive equal pressure during molding at high temperature and pressure, which may result in a decrease in density and deterioration of magnetism. 50 If the grain size is less than 150 μm, it may not be possible to achieve a uniform grain size to minimize core loss at frequencies below 1000 Hz. 50 If the particle size exceeds 300 μm, the number of particles larger than the particle size optimum for magnetism will be in the majority of the total particles, and there is a risk of the magnetic properties being deteriorated.
[0023] The soft magnetic iron-based powder according to one embodiment of the present invention may contain, by weight percent, Si: more than 2%, Al: more than 0.02%, Mn: more than 0.05%, O: more than 0% but less than 0.1%, and the balance being Fe and unavoidable impurities. The reasons for limiting the component range of each alloy element are described below.
[0024] The Si content may exceed 2% by weight. Silicon is an essential element for increasing the resistivity of iron-based powder. According to the present invention, since the silicon content exceeds 2% by weight, the ferrite phase can be maintained even during high-temperature compaction, and the particle size of the powder can be almost the same as that of the powder in the part compacted at high temperature and / or high pressure. If the silicon content is less than 2% by weight, the particle sizes of the powder and the powder in the part compacted at high temperature and / or high pressure are significantly different, making it difficult to ensure the appropriate particle size of the powder itself.
[0025] The Al content may exceed 0.02% by weight. Al plays the same role as Si in increasing the resistivity of the iron-based powder. Furthermore, Al is actively added as an element for appropriately controlling the amount of other impurities so that the magnetic properties of the iron-based powder can be improved. From this viewpoint, according to the present invention, it is preferable that Al is added in an amount exceeding 0.02 wt %. From the viewpoint of controlling impurities such as O and S, it is more preferable that Al is added in an amount exceeding 0.3 wt %.
[0026] The Mn content may exceed 0.05% by weight. Mn plays the same role as Si in increasing the resistivity of the iron-based powder. Also, Mn is actively added as an element that forms oxides and sulfides to improve the magnetic properties of the iron-based powder and prevents impurities in the iron-based powder from minimizing the size of crystal grains. From this perspective, according to the present invention, Mn is preferably added in an amount exceeding 0.05 wt %. In order to dissolve oxygen and sulfur in the steel as oxides or sulfides, Mn is preferably added in an amount exceeding 0.2 wt %.
[0027] The O content may be more than 0% by weight and less than 0.1% by weight. O is a component that increases continuously when high-temperature processes are performed during the production of iron-based powder. The lower the O content in the final part molded at high temperature and / or pressure, the better the magnetic properties. According to the present invention, the upper limit of O is limited to 0.1 wt%. However, a suitable amount of O combines with Si, Al, Mn, etc. on the surface of the iron-based powder to form an oxide layer that exhibits electrical insulation. According to the present invention, when a part is manufactured using an iron-based powder having an insulating layer containing Si, Al, Mn, and O on the surface, it is possible to manufacture a soft magnetic part with reduced iron loss. Taking this into consideration, according to the present invention, the content of O exceeds 0 wt%.
[0028] According to the present invention, in addition to the above-mentioned range of the alloy composition, the following correlations of the alloy components can be selectively satisfied. [Si] / [Al]>2
[0029] Here, [Si] and [Al] mean the weight percent of each element. Al can increase resistivity and reduce the S content, but Al easily bonds with O at high temperatures, which causes a problem of excessive O content during the process of manufacturing iron-based powder. In this case, the higher the Si content relative to the Al content, the easier it is to suppress the increase in O content due to Al. In addition, if the Al content is high in the insulating layer containing Si, Al, Mn, and O on the surface of the iron-based powder, there is a problem of high iron loss. In order to solve the above-mentioned problems, according to one example of the present invention, the composition can be controlled so that the Si content is more than twice the Al content.
[0030] According to one example, D 10 and D. 90 The difference between [Si]+[Al]+[Mn] in the powder may be less than 10% by weight. Here, [Si], [Al], and [Mn] refer to the weight percent of each element. In the case of Si, Al, and Mn, which are elements that greatly increase resistivity, it is very effective in increasing resistivity as the alloy increases. However, if the concentration changes significantly depending on the particle size of the powder, when manufacturing soft magnetic parts with complex shapes, the magnetic properties may not be uniform, and some parts may show inferior magnetic properties compared to normal materials.
[0031] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude them. Since any engineer of a normal manufacturing process would know about these impurities, the contents of all of them are not specifically mentioned in this specification.
[0032] The technical significance of the impurity elements and the ranges of their contents will be described below. However, it should be noted that the impurity elements and the ranges of their contents described below are not essential components for obtaining the soft magnetic iron-based powder and soft magnetic parts targeted by the present invention, are described merely to aid in understanding the present invention, and do not particularly limit the technical concept of the present invention.
[0033] The C content may be less than 0.01% by weight. C is an element that is inevitably added during the production of iron-based powder. When added in large amounts, C forms precipitates, hinders the movement of magnetic domains, and adversely affects magnetism. Therefore, it is preferable to limit the C content to less than 0.01% by weight. More preferably, if the C content is less than 0.004% by weight, it is excellent in iron loss and does not deteriorate even during annealing at a low temperature of 300°C or less, which is preferable.
[0034] The N content may be less than 0.01% by weight. N is an element that is inevitably added during the production of iron-based powder. When added in large amounts, N forms precipitates, hinders the movement of magnetic domains, and adversely affects magnetism. In particular, N exists in a gaseous state at high temperatures, and there is a problem of forming gas outlets in the steel, so it is preferable to limit the amount of N added to less than 0.01% by weight. More preferably, if the N content is less than 0.004% by weight, it is excellent in iron loss and does not deteriorate even during annealing at a low temperature of 300°C or less, so this is preferable.
[0035] The S content may be less than 0.05% by weight. S is an element that is inevitably added when manufacturing iron-based powders. When added in large quantities, S liquefies to FeS at high temperatures, making manufacturing more difficult, and forms precipitates with Mn, Cu, etc., hindering the movement of magnetic domains, thereby adversely affecting magnetism. Therefore, it is preferable to limit the S content to less than 0.05% by weight. In particular, S segregates at the interface when added in large quantities, impairing interface stability, so it can be more preferably limited to less than 0.01% by weight. S can more preferably be limited to less than 0.003% by weight in order to reduce iron loss.
[0036] The Ti content may be less than 0.01% by weight. Ti is an element that is inevitably added during the production of iron-based powders. When added in large quantities, Ti combines with oxygen to form coarse oxides in molten steel when the molten steel is in the liquid phase at high temperatures, and then forms carbides and nitrides that deteriorate the magnetic properties even after the parts are manufactured. Therefore, it is preferable to limit the Ti content to less than 0.01 wt.%.
[0037] The Mg content may be less than 0.05% by weight. Mg is an element that is inevitably added during the production of iron-based powders. When added in large quantities, Mg combines with sulfur or oxygen to form inclusions in molten steel when the molten steel is in the liquid phase at high temperatures, and the inclusions then grow to form oxides and sulfides that degrade the magnetic properties even after the parts are manufactured. Therefore, it is preferable to limit the Mg content to less than 0.05 wt.%.
[0038] The method for producing soft magnetic iron-based powder according to the present invention will be described in detail below. The method for producing iron-based powder according to the present invention may use a method of cooling and solidifying a high-temperature liquid phase. In general, when a solid metal compound changes into a liquid phase, it is expected that there will be no significant change in the components in the liquid phase, but this is not the case. The composition of the components in the liquid phase is determined by the thermodynamic interrelationships of Si, Al, Mn, C, N, S, Ti, Mg, etc., which are molten in the liquid phase. For example, when the Si content is high, the attractive and / or repulsive forces between each element change significantly due to Si, resulting in a large change in the components in the local range of the liquid phase molten steel. As an example, when the liquid phase molten steel is solidified while being cooled, dendrites that grow from the surface to the inside can be formed by Si, Al, Mn, etc. In the iron-based powder in which dendrites are formed, there is a risk that a large difference in components between the interface and the inside of the dendrites will occur depending on the size and / or shape of the dendrites.
[0039] The method for producing soft magnetic iron-based powder according to the present invention can minimize the change in the components of the iron-based powder. The method for producing soft magnetic iron-based powder according to an example may include the steps of cooling molten steel containing, by weight, Si: more than 2%, Al: more than 0.02%, Mn: more than 0.05%, O: more than 0% and less than 0.1%, and the balance Fe and unavoidable impurities from 1500°C to 1000°C within 10 minutes to solidify, cooling from 1000°C to 900°C or less within 100 minutes, heating to liquidize, and atomizing to powder. After the cooling step, the method may further include a process of deforming, physically cutting, or crushing.
[0040] According to one embodiment of the present invention, the ratio of the surface area (S) of the solidified molten steel to the volume (V) during the solidification step is 4 cm -1 The S / V ratio may be less than 4 cm. -1 If the S / V ratio exceeds 0.3 cm, the surface area that reacts with oxygen in the air at high temperatures to form a thick oxide layer becomes excessively large. As a result, the oxide layer that is formed is transferred to the inside along the grain boundaries, which greatly increases the oxygen concentration in the steel and may cause composition deviation. From this perspective, the S / V ratio is more preferably 0.3 cm-1 Less than or equal to 0.11 cm, more preferably -1 However, the solidified molten steel is further heated to liquefy, so when the liquidus time is taken into consideration, the S / V ratio is 0.08 cm -1 More preferably, it is equal to or greater than this.
[0041] The soft magnetic part according to the present invention can be manufactured by compression molding soft magnetic iron-based powder at high temperature and / or high pressure. The soft magnetic part according to an example may include soft magnetic iron-based powder containing, by weight percent, more than 2% Si, more than 0.02% Al, more than 0.05% Mn, more than 0% but less than 0.1% O, with the remainder being Fe and unavoidable impurities, satisfying [Si] / [Al]>2, and an insulating layer containing Si, Al, Mn, and O on the interface between the soft magnetic iron-based powder. The reasons for limiting the composition of the iron-based powder alloy are as described above, and will not be described here for convenience.
[0042] The soft magnetic part according to the present invention includes an insulating layer on the interface between soft magnetic iron-based powder particles, the insulating layer containing Si, Al, Mn, and O. The insulating layer in the soft magnetic part is obtained by compressing iron-based powder having an insulating layer formed on its outer surface at high temperature and / or pressure, without performing a separate insulating coating as described above. According to one example, the thickness of the insulating layer may be 10 to 50 nm. If the thickness of the insulating layer is less than 10 nm, the insulation properties may be insufficient, and eddy current loss may increase, which may increase iron loss. If the thickness of the insulating layer exceeds 50 nm, the amount of oxygen in the steel may increase significantly, which may be detrimental to magnetic properties. The average size of the soft magnetic iron-based powder in the soft magnetic component according to one embodiment of the present invention may be 150 to 500 μm. If the average size is less than 150 μm, the hysteresis loss cannot be sufficiently reduced, and the iron loss may not be sufficiently reduced in the low frequency range of 1000 Hz or less. On the other hand, if the average size exceeds 500 μm, the density of the component may be low, and the magnetism may be deteriorated.
[0043] According to one embodiment of the present invention, G 95 is less than 500 μm, and G 50The thickness may be 150 to 300 μm. 95 If the thickness is more than 500 μm, the density of the parts will be low and the magnetic properties may deteriorate. 50 If the diameter is less than 150 μm, the particle size of the iron-based powder in the component may not be uniform enough to minimize the iron loss at frequencies below 1000 Hz. 50 If the size exceeds 300 μm, the number of iron-based powder particles larger than the size optimal for magnetism will be in the majority of the total iron-based powder, and there is a risk of the magnetic properties being deteriorated.
[0044] According to one example, G 10 and G 90 The difference between [Si]+[Al]+[Mn] in the powder composition may be less than 10% by weight. Here, [Si], [Al], and [Mn] refer to the weight percent of each element. In the case of Si, Al, and Mn, which are elements that greatly increase resistivity, increasing the alloy is very effective in increasing resistivity. However, if the concentration varies significantly depending on the particle size of the powder, the magnetic properties may not be uniform when manufacturing soft magnetic parts with complex shapes, and some parts may exhibit magnetic properties inferior to those of normal materials. In a soft magnetic part according to an embodiment of the present invention, the area ratio of soft magnetic iron-based powder having a major axis length to minor axis length ratio of 50% or more may be 1 to 2. If the major axis length to minor axis length ratio exceeds 2, the particle shape significantly deviates from a spherical shape, which may cause local component deviations during powder formation and result in deterioration of magnetism.
[0045] The soft magnetic component according to the present invention can sufficiently reduce iron loss in a frequency range of 1000 Hz or less. According to one example, the iron loss may be 40 W / kg or less at 1 T and 400 Hz. According to another example, the iron loss may be 140 W / kg or less at 1 T and 1000 Hz. The soft magnetic part according to the present invention has excellent magnetic properties, and according to one example, the magnetic flux density (B 100 ) may exceed 1.1T. The soft magnetic component according to the present invention has a high resistivity, and according to one example, the resistivity may exceed 40 μΩ·cm.
[0046] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention, since the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred from them.
[0047] {Example} The steel having the composition shown in Table 1 below is produced into liquid molten steel using a conventional converter. The liquid molten steel is then poured into a converter with a surface area (S) to volume (V) ratio of 4 cm -1 The material was cooled from 1500°C to 1000°C within 10 minutes, solidified, and cast as shown below. The cast semi-finished product can be called a slab, bar, or hot coil depending on its shape or thickness. It was then cooled from 1000°C to 900°C within 100 minutes. The cooled semi-finished product was then used as is, or further processed by deforming, physically cutting, crushing, etc. Then, it was heated to 1500°C or higher to liquidize, and atomized and powdered by a conventional method to produce iron-based powder. In Table 1, [Si] and [Al] mean the weight percentage of each element.
[0048] [Table 1]
[0049] The average particle size of the powdered iron-based powder particles in each example, D 95 , D 50 , D 90 , D 10 The particle sizes of each of the examples were measured and are shown in Table 2. 90 , D 10 The composition of the particles is shown in Table 3. In Table 3, [Si] + [Al] + [Mn] means the weight percentage of each element.
[0050] [Table 2]
[0051] [Table 3]
[0052] The iron-based powder of each embodiment that satisfies the alloy composition and particle size defined by the present invention includes an insulating layer containing Si, Al, Mn, and O on the outer surface, has an iron loss of 75 W / kg to 110 W / kg at 1 T and 400 to 1000 Hz, and a magnetic flux density (B 100 ) was 1.0 to 1.5T.
[0053] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and a person having ordinary knowledge in the art can understand that various changes and modifications are possible within the scope of the concept and scope of the claims described in this specification. [Industrial Applicability]
[0054] According to the present invention, it is possible to provide a soft magnetic iron-based powder that can be applied to various industrial fields such as motor cores, a manufacturing method thereof, and a soft magnetic part.
Claims
1. An insulating layer containing Si, Al, Mn, and O on an outer surface thereof, The insulating layer has a thickness of 10 to 50 nm; In weight percent, Si: more than 2% and not more than 4%, Al: more than 0.02% and not more than 1.0%, Mn: more than 0.05% and not more than 0.6%, O: more than 0% and less than 0.1%, and the balance being Fe and unavoidable impurities. [Si] / [Al]>2 is satisfied; A soft magnetic iron-based powder having an average particle size of 150 to 400 μm. (The above [Si] and [Al] represent the weight percentages of each element.)
2. D 10 and D. 90 2. The soft magnetic iron-based powder according to claim 1, characterized in that the difference between [Si] + [Al] + [Mn] at is less than 10% by weight. (The above [Si], [Al], and [Mn] represent the weight percentages of each element.)
3. D 95 is less than 500 μm, and D 50 2. The soft magnetic iron-based powder according to claim 1, wherein the particle size is 150 to 300 μm.
4. A step of cooling the molten steel, which is composed of, by weight percent, Si: more than 2% but not more than 4%, Al: more than 0.02% but not more than 1.0%, Mn: more than 0.05% but not more than 0.6%, O: more than 0% but less than 0.1%, and the balance being Fe and unavoidable impurities, to 1500°C to 1000°C within 10 minutes to solidify the molten steel; Cooling the material from 1000° C. to 900° C. in less than 100 minutes; A step of heating to a liquid phase; and atomizing the mixture into powder, In the solidification step, the ratio of the surface area to the volume of the solidified molten steel is 4 cm -1 2. The method for producing soft magnetic iron-based powder according to claim 1, wherein the method is as follows:
5. a soft magnetic iron-based powder consisting of, by weight percent, Si: more than 2% and not more than 4%, Al: more than 0.02% and not more than 1.0%, Mn: more than 0.05% and not more than 0.6%, O: more than 0% and less than 0.1%, with the balance being Fe and unavoidable impurities, satisfying [Si] / [Al]>2; an insulating layer containing Si, Al, Mn, and O on an interface between the soft magnetic iron-based powders; The insulating layer has a thickness of 10 to 50 nm; The soft magnetic iron-based powder has an average particle size of 150 to 500 μm, A soft magnetic part characterized by having a magnetic resistance of 140 W / kg or less at 1 T and 1000 Hz.
6. G 10 and G 90 6. The soft magnetic component according to claim 5, wherein the difference between [Si] + [Al] + [Mn] in is less than 10% by weight. (The above [Si], [Al], and [Mn] represent the weight percentages of each element.)
7. 6. The soft magnetic part according to claim 5, wherein the area ratio of the soft magnetic iron-based powder having a ratio of the major axis length to the minor axis length of 1 to 2 is 50% or more.
8. G 95 is less than 500 μm, and G 50 The soft magnetic part according to claim 5, characterized in that the thickness is 150 to 300 μm.
9. 6. The soft magnetic part according to claim 5, characterized in that it has a magnetic field strength of 40 W / kg or less at 1 T and 400 Hz.
10. Magnetic flux density (B) at 50 Hz and 10,000 A / m 100 6. The soft magnetic component according to claim 5, wherein the magnetic field strength exceeds 1.1 T.
11. 6. The soft magnetic component according to claim 5, characterized in that the resistivity exceeds 40 μΩ·cm.
Citation Information
Patent Citations
Soft magnetic composite material and preparation method thereof
CN102789859A
Insulation coating treatment method for increasing pressed density of iron-based soft magnetic composite material
CN108183012A
Process for the production of a soft-magnetic body by powder metallurgy
DE3439397A1
Manufacture of "sendust(r)" plate having superior magnetic characteristic
JP1985204833A
Soft magnetic powder, powder granules, dust core, electromagnetic component, and method for producing dust core
JP2012009825A